Unaccounted variability in NH3 agricultural sources detected by IASI contributing to European spring haze episode. Issue 10 (23rd May 2016) - Fortems‐Cheiney, A.; Dufour, G.; Hamaoui‐Laguel, L.; Foret, G.; Siour, G.; Van Damme, M.; Meleux, F.; Coheur, P.‐F.; Clerbaux, C.; Clarisse, L.; Favez, O.; Wallasch, M.; et al.
Abstract: Ammonia (NH3 ), whose main source in the troposphere is agriculture, is an important gaseous precursor of atmospheric particulate matter (PM). We derived daily ammonia emissions using NH3 total columns measured from the Infrared Atmospheric Sounding Interferometer (IASI) on board Metop‐A, at a relatively high spatial resolution (grid cell of 0.5° × 0.5°). During the European spring haze episodes of 24–31 March 2012 and 8–15 March 2014, IASI reveals NH3 total column magnitudes highlighting higher NH3 emissions over central Europe (especially over Germany, Czech Republic, and eastern France) from the ones provided by the European reference European Monitoring and Evaluation Programme inventory. These ammonia emissions exhibit in addition a large day‐to‐day variability, certainly due to spreading practices. The increase of NH3 emissions in the model, that reaches +300% locally, leads to an increase of both NH3 and PM2.5 surface concentrations and allows for a better comparison with independent measurements (in terms of bias, root‐mean‐square error, and correlation). This study suggests that there are good prospects for better quantifying NH3 emissions by atmospheric inversions. Key Points: Strong potential of IASI for deducing NH3 daily emissions High NH3 emissions revealed over central Europe Strong impact of NH3 emissions on pollution particle formation